THE STUDY OF STUDENTS’ WRITING ABILITY ON GRADE ELEVEN OF SMK NEGERI 1 KAMBOWA - Zahira Zahira; Sanaria Maneba; Nety Nety (English Education Journal, 2021)
The problem statement in this research was “How was the level writing ability of students at grade eleven SMK Negeri 1 kambowa?” The objective of this research was to investigate the students level ability in writing. This research used a quantitative method with a descriptive design. Source of data in this research was student at grade XI of SMK Negeri 1 Kambowa. Sample was taken by using saturated sample tehnique, the number of sample was 30 students. Instrument used in this study was a test. The data obtained were analyzed by descriptive analysis and inferential analysis in the form of t-test. The result showed that the students’ writing ability were still lacking. This proved by the t-test that t-count was greater than T- table (4,054>1,699). Based on Hypothesis testing, it means that H0 was rejected and Ha was accepted. So, it could be concluded that the students writing ability on grade eleven at SMK Negeri 1 Kambowa is not high.